The optimality in non-coalitional games: review of the approaches - Vilkas, E. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Вилкас. Оптимальность в бескоалиционных играх: обзор подходов E. Vilkas. Optimalumas nekoaliciniuose lošimuose: koncepcijų apžvalga